Robin Hood spins gold (New York : Random House, 1979)
Robin Hood and Little John don disguises in order to convince the king they can protect his gold by spinning it into straw.
At head of title: Disney's.
"Originally published in Denmark as Robin Hood spinder guld by Gutenberghus Bladene, Copenhagen."--Title page.
Keywords: Children's stories